Basal-pyramidal dislocation lock in deformed magnesium. (June 2017) - Li, B.; Zhang, Q.W.; Mathaudhu, S.N.
Abstract: Dislocations and stacking faults in unalloyed magnesium processed by equal-channel-angular-extrusion are investigated by transmission electron microscopy. Stacking faults as wide as hundreds of nanometers and complex dislocation configurations are revealed, which creates diffraction contrast that is challenging to interpret. To elucidate the dislocation interaction, atomistic simulations are conducted. The concomitant results show that the leading partial dislocations on the basal and the pyramidal planes interact and form a dislocation lock, creating the diffraction contrast observed in experiments. The dislocation locks may act as obstacles to dislocation glide and contribute to hardening. Graphical abstract: